MEREPRESENTASI KEARIFAN LOKAL Framing Tradisi Nangguak Tebat Di Media Daring - Adde, Exsan; Dewi, Ramadhani Utami; Laksmono, Vidyardi (PRoMEDIA, 2025)
This study examines the framing of the Nangguak Tebat tradition by five Indonesian online media (Kompas.com, Detik.com, Bisik.id, Narasiberita.co.id, Jejakdaerah.id) in May 2025. Using qualitative content analysis with Entman's Framing theory, Stuart Hall's Representation theory, and CuDA, this study reveals how the media collectively represent this tradition positively, highlighting local wisdom, social, and ecological values. Nevertheless, each media outlet demonstrates different framing emphases, ranging from aspects of solidarity, indigenous identity, environmental sustainability, tourism potential, to food security. These findings underscore the significant role of media in constructing public understanding of local culture and the importance of fair and empowering representation.